2002
DOI: 10.1509/jppm.21.2.275.17591
|View full text |Cite
|
Sign up to set email alerts
|

Marketing Research and Public Policy: The Case of Slotting Fees

Abstract: The authors extend their appreciation to Paul Bloom and Joseph Cannon, who provided valuable feedback and insights regarding this article and permitted the use of the survey data that made this article possible. 1 Although frequently used interchangeably, slotting fees typically refer to up-front cash payments, whereas allowances reflect free or discounted orders for products (Cannon and Bloom 1991).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0

Year Published

2004
2004
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(44 citation statements)
references
References 15 publications
(24 reference statements)
0
44
0
Order By: Relevance
“…Due to the transfer of the power of industry to the retailer, the practice of slotting fees represents a strategy for the fabricant to influence the retailer to have the products distributed, exposed, or stored at the sales point. This value is paid by the industry, and it can be funded with money or as subsidy, discounts in the orders or bonus of products (Wilkie et al, 2002). However, the conflicts between retailer and supplier can generate greater volume of sales, greater profitability and reduction of time of supplying to every member of the chain.…”
Section: Answerofthecostumermentioning
confidence: 99%
“…Due to the transfer of the power of industry to the retailer, the practice of slotting fees represents a strategy for the fabricant to influence the retailer to have the products distributed, exposed, or stored at the sales point. This value is paid by the industry, and it can be funded with money or as subsidy, discounts in the orders or bonus of products (Wilkie et al, 2002). However, the conflicts between retailer and supplier can generate greater volume of sales, greater profitability and reduction of time of supplying to every member of the chain.…”
Section: Answerofthecostumermentioning
confidence: 99%
“…However, they are often not passed on to consumers (Hoyt, 1997); and may induce the trade to stock-pile a product in order to take advantage of the temporary price reductions, which usually shifts business from the future to the present (Buzzeli, et al, 1990;sellers, 1992); retailers could resist Everyday Low Pricing (EDLP) program by manufacturers (Manning, 1994) and the retailer never spends advertising accruals (Everett, 1987;Blakkhan, 1983) and could be diverted (Berry, 1992;Hoyt, 1996) while a vast majority of retailers think that trade promotions should serve to increase sales and profits of entire product categories without concern for whether a manufacturer's specific brand benefits from the trade promotion (Hoyt, 1997). Fortunately for the trade, these abuses are being checked (Abraham and Lodish, 1990;Neff, 1995) The major types of trade allowances are slotting allowance (Hoyt, 1997;Cannon and Bloom, 1991;Liessie, 1990;Benezra, 1995;Wilkie, et al, 2002;Ante, 1989;Tienowitz, 1999;Bloom, et al, 2000); bill-back allowances, exit fees, drop-ship allowance, co-operative advertising (Elkin, 1999;Rigg, 1990) etc.…”
Section: Trade Allowancementioning
confidence: 99%
“…While manufacturers and retailers agree that the number of new products introduced is a key force in the widespread use of slotting fees (Wilkie et al 2002;Bloom et al 2000), Bloom et al (2000) find that retailers do not believe that slotting fees are related to the opportunity cost of shelfspace. Wilkie et al (2002) also find no support for the growth of private label brands as a rationale for the growth of slotting allowances. Basically, in these survey-based studies, it appears that retailers do not want to accept their role in the emergence of slotting allowances, but want to blame manufacturers.…”
Section: A1 Slotting Allowances Help Efficient Allocation Of Scarce mentioning
confidence: 99%
“…But slotting allowances are extremely controversial and there is very little consensus either among practitioners, regulators or researchers as to the true role of slotting allowances in facilitating new product introductions (Bloom et al 2000 andGundlach et al 2002). While some theorists and practitioners have suggested that slotting allowances are anti-competitive, others have argued that slotting allowances serve to enhance efficiency of market outcomes.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation